(untitled) (Journal of Biomedical Investigation, 2025)
Background: University teachers (lecturers) face significant stress from their teaching, research, and service duties which negatively impact their health and well-being. Mindfulness, characterized by present-moment awareness and non-judgmental acceptance, can reduce stress, alleviate anxiety and depression, and improve job satisfaction, performance, and work-life balance. Aim: To examine how mindfulness influences work stress and overall well-being of lecturers at the Nnamdi Azikiwe University, Nnewi Campus, Nigeria. Materials And Methods: This was a cross-sectional study that involved 73 lecturers, with a mean age of 45.7±9.945.7 years. The Five Facets of Mindfulness, work stress, Work-Related Quality Of Life Scale, and WHO-5 Well-Being Questionnaires were used to assess mindfulness, stress level, and well-being respectively. Data was analyzed with descriptive statistics and Spearman’s rank correlation with level of significance set at p<0.05. Results: No significant differences were found in mindfulness (K = 4.213, p = 0.837) or work stress (K = 10.128, p = 0.256) among lecturers of different departments. Male lecturers reported significantly higher work-related quality of life and general well-being than females (WRQoL: U = 429.5, p = 0.023; WHO-5: U = 362.5, p = 0.002). However, no significant correlations were observed among mindfulness, work stress, well-being, age, or years of lecturing experience. Conclusion: The findings suggest that mindfulness, stress levels, and well-being are not significantly correlated. While gender differences in well-being were evident, other demographic factors such as age and professional experience showed no significant influences.